Comparative analysis of corporate social responsibility practices of selected Philippine conglomerates - Buera, Jean Agnes D. (UP Los Baños Journal, 2012)
This study analyzed corporate social responsibility pratices disclosed by selected conglomerates namely: Lopez Group of Companies; Petron Corporation; Philippine Long Distance Tel. Inc.; and San Miguel Corporation. By combining the performance indicators, the aspects, and the extent of emphasis given on them by the conglomerates' Social Responsibilty (CSR) practices on the Global Reporting Initiative's (GRI) Social Performance Indicator. With 63% of the total number of CSR activities, the highly prioritized aspects of the Social Performance Indicator was the Community providing that the core of CSR in the Philippines is still on community involvement. As such, it is important to have a measure that reflects the approach used by the conglomegers to manage their impacts, both negative and positive, on the communities in which they operate. The impacts of operation refer to the social implications, such as community, health, and safety, education, livelihood projects, resettlements, local, culture, and cultural heritage. CSR demands that commercial success be gained through positive practices that aim to promote general welfare. Therefore, these business conglomerates should act in consonance with the country's social development, whether through community assistance, educatioanl programs, employee development, or business innovations for the welfare of the society. The results also affirmed the Community-Building Theory which allows the role of public relations as tool for bringing back the sense of community in the society and giving way to more CSR activities promoting this cause. After all, sustainabilty cannot be achieved without mutually beneficial relationships as well as the people's participation.